The Influence of Product Quality, Packaging, and Brand Image on Purchase Decisions: The Mediating Role of Perceived Value in MSME Bakery Context - Ababil Karhoma Wijaya; Handri Dian Wahyudi; Ely Siswanto; Misbahul Munir; Murni Binti Yusof (Journal of Social Work and Science Education, 2026)
Micro-small-medium enterprises (MSMEs) in the food sector often struggle to compete with established brands. This study examines how product quality, brand image, and packaging influence purchase decisions, with perceived value as a mediator, in the context of MSME bakery in Indonesia. Data from 100 consumers were analyzed using PLS-SEM in quantitative method. The results indicate that product quality, product packaging, and perceived value significantly and positively affect purchase decisions. Product quality and product packaging also exert significant effects on perceived value, whereas brand image does not. Mediation analysis reveals that perceived value mediates the relationship between product quality and purchase decision, as well as between product packaging and purchase decision, but not between brand image and purchase decision. These findings indicate that consumers prioritize tangible cues, such as product quality and packaging design over symbolic brand associations when evaluating bread MSME products. The study concludes that improving product quality and packaging is crucial for enhancing perceived value and driving purchasing behavior, while brand development remains a long-term strategic goal. Future research should involve multiple MSMEs and additional constructs such as customer satisfaction, brand trust, and price fairness to expand generalizability within Indonesia’s food industry context.